THE USE OF DNA - TECHNOLOGIES FOR CREATION AND IMPRVEMENT OF INITIAL STOCK FOR BREEDING OF COLD TOLERANT RICE VARIETIES - M. A. Skazhennik; V. A. Dzuba; V. C. Kovalyov; E. V. Dubina; I. N. Chukhir; E. G. Savenko; T. S. Pshenitsyna (Зерновое хозяйство России, 2018)
For Russia countries with a temperate climate, with direct sowing of rice increase of cold tolerant varieties in seed germination and shoot formation are important. This trait allows to begin rice sowing earlier using for plant growing the favorable period by temperature to obtain optimum shoots by density that gives the chance to realize potential efficiency of varieties. A research objective is to create and estimate the initial stock resistant to low positive temperatures for use it for breeding of new cold tolerant rice varieties.Display of molecular markers - is neutral in relation to a phenotype and they can be found out at any stage of development of plants in ontogenesis. Methods of DNA-genotipirovanija and PCR analysis by means of molecular markers allow accelerating carrying over of the necessary genes in the course of breeding and to provide creation of new varieties with a complex of the set properties Therefore the role of biotechnological methods is important at creation new cold tolerant varieties.According to results of PCR analysis by use of SSR - marker lines of rice with dominant alleles of cold resistance genes were screened. Double haploids were obtained by anther culture method in vitro and resistant forms were found. Plants with economically valuable traits were screened. All-round evaluation of obtained material gave the possibility to find initial stock for use breeding process in future for release of new cold resistant rice varieties.